Behavior of a mobile robot with symmetrical structure of mecanium wheels when movement along a curvolinear trajectory - S. A. Pauliukavets; A. A. Velchenko; A. A. Radkevich (Системный анализ и прикладная информатика, 2024)
The article presents a comparative analysis of two variants of symmetrical placement of omnidirectional mecanum wheels in a mobile robot. The modeling of the mobile robot behavior with two symmetrical variants of mecanum wheel arrangement along curvilinear trajectories in the MATLAB Simulink environment is considered. Graphs of the robot center trajectories in the X–Y axes are obtained for two variants of symmetrical mecanum wheel configurations when moving along the trajectories of a lemniscate, ellipse, hypotrochoid, and track. Dependences of the robot position errors in the X–Y axes on time are obtained for two variants of wheel topologies when moving along four trajectories. Dependences of the robot body rotation angle deviation on time are analyzed for two variants of wheel topologies when moving along four curvilinear trajectories. The comparative analysis made it possible to give recommendations on movement along the ellipse and lemniscate, which are characterized by smaller position errors and deviations in the rotation angle compared to more complex curves.